THE RELEVANCE OF QUALIFIED PERSONNEL IN THE DIGITAL ECONOMY (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
The problem of personnel in the digital economy is one of the topics that have gained importance in recent years. As technology and innovation continue to grow, it is critical that students and the workforce have the skills and knowledge they need for the digital economy.